Chile : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that Chile's economic fundamentals remain sound and have improved through the evolution of the policy regime in recent years. Yet the country is operating in a difficult environment for several years, now coping with a sequence of negative shocks. Real GDP grew by 2.8 percent in 2001, as weakening domestic demand was offset by a strong expansion of net export volumes. With a substantial decline in Chile's terms of trade, however, the external current account deficit has widened moderately, to about 2 percent of GDP.